Blood CXCR3+ CD4 T Cells Are Enriched in Inducible Replication Competent HIV in Aviremic Antiretroviral Therapy-Treated Individuals - Banga, Riddhima; Procopio, Francesco A.; Ruggiero, Alessandra; Noto, Alessandra; Ohmiti, Khalid; Cavassini, Matthias; Corpataux, Jean-Marc; Paxton, William A.; Pollakis, Georgios; Perreau, Matthieu (Frontiers in Immunology, 2018)
We recently demonstrated that lymph node (LN) PD-1+/T follicular helper (Tfh) cells from anti-retroviral therapy (ART) treated HIV-infected individuals were enriched in cells containing replication competent virus. However, the distribution of cells containing inducible replication competent virus has been only partially elucidated in blood memory CD4 T-cell populations including the Tfh cell counterpart circulating in blood (cTfh). In this context, we have investigated the distribution of 1) total HIV-infected cells and 2) cells containing replication competent and infectious virus within various blood and LN memory CD4 T-cell populations of conventional ART (cART) treated HIV-infected individuals. In the present study, we show that blood CXCR3-expressing memory CD4 T cells are enriched in cells containing inducible replication competent virus and contributed the most to the total pool of cells containing replication competent and infectious virus in blood. Interestingly, subsequent proviral sequence analysis did not indicate virus compartmentalization between blood and LN CD4 T-cell populations, suggesting dynamic inter-changes between the two compartments. We then investigated whether the composition of blood HIV reservoir may reflect the polarization of LN CD4 T cells at the time of reservoir seeding and showed that LN PD-1+ CD4 T cells of viremic untreated HIV-infected individuals expressed significantly higher levels of CXCR3 as compared to CCR4 and/or CCR6, suggesting that blood CXCR3-expressing CD4 T cells may originate from LN PD-1+ CD4 T cells. Taken together, these results indicate that blood CXCR3-expressing CD4 T cells represent the major blood compartment containing inducible replication competent virus in treated aviremic HIV-infected individuals.